ChemInform Abstract: "Water‐in‐Salt" Electrolyte Enables High‐Voltage Aqueous Lithium‐Ion Chemistries. Issue 7 (January 2016) - Suo, Liumin; Borodin, Oleg; Gao, Tao; Olguin, Marco; Ho, Janet; Fan, Xiulin; Luo, Chao; Wang, Chunsheng; Xu, Kang
Abstract: Highly concentrated aqueous solutions of LiN(SO2 CF3 )2 (5—20 M at 25 °C) are used as an electrolyte in a CR2032‐type coin cell containing either LiMn2 O4 or LiNi0.8 Co0.15 Al0.05 O2 as the cathode and Cu‐leached Mo6 S8 Chevrel phase as the anode separated by glass fiber fabrics.